Health and safety: enhancing community-based Education modulers of preparedness for floodrelated communicable diseases in Kelantan - Mohammad, Wan Mohd Zahiruddin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2017)
In Phase 1 (between August and October 2015, situational analysis were done in assessing and exploring baseline knowledge, attitude and preventive practices (KAP) of the affected communities with regards to communicable diseases related to flood. Baseline community surveys were conducted using a pre-validated KAP questionnaire through g_uided interviewed-based technique among 300 villagers. Raw total scores from each section of KAP were converted to percentage scales for analysis while four focus group discussions (FGD) were performed to explore their coping and experiences in the flood disaster. In Phase 2 (between November 2015 and February 2016), health education materials were developed through series of workshop and then were evaluated through a community intervention. These involved revising existing health education materials, creating new materials tailored to the community and getting feedback from stakeholders. Customized modules that focusing on major flood-related communicable diseases and comprising of printed materials and audio-visual information kits were eventually developed which included 2 series of health education flip charts, 2 series of PowerPoint slides for health talk, 3 series of health education flyers, 10-minute video with captions on flood-health hazards, diseases and prevention messages and other complementary public health information. A non-randomized community-controlled trial was then conducted to determine effectiveness of the community-based health education modules. The delivery channels of the health modules were conducted at least two weeks before the forecasted flood seasons in that year. Two strategies were applied: targeted small group health education sessions which comprised 20-25 persons each, and mass dissemination of public information health education materials. Results Three hundreds repondents were interviewed with a mean age of 45.1 years old (SD=17.34) and mainly those with secondary school education (n=166, 55.3%). Taking mean scores below 60% as unsatisfactory, all knowledge domains, attitude and selected pratices (drinking water and protective habit) need further concern. Between 90. 7 to 96.3% agreed that they were more likely to practice preventive measures if given proper information and personal protective tools (e.g soap, hand sanitizer, face mask etc). Between 72.2 - 95.3% agreed that current materials of health education on flood related diseases were useful but interactive small group discussions and demonstrations were also suggested by them. There were 129 and 101 respondents within the intervention community who were participated in the repeated surveys at 1-week and 1-month post intervention KAP assessments respectively while another 125 in the controlled group. Table 1 shows there were statistically significant improvements in all knowledge components (type of diseases, common symptoms, methods of transmission, susceptible and risk factors, and danger signs) from 9.4% to 52.6% (P<0.001) while there was a 10% increment (P<0.001) in attitude scores toward preventing behaviours on flood-related communicable diseases among the intervention community. There was a slight reduction in most domains at 1-month post intervention; however all mean scores were still higher than at the baseline pre intervention stage. When compared to control community at post-1 month, statistically significant difference in knowledge scores were shown between 15.4% and 35.4% (P<0.001) on types of diseases, common symptoms and susceptible/ risk factors domains. There were siQnificant improvements on the practice domains at post 1-month in the practice of drinkinQ safe water and protective habits (P<0.001 and P<0.006 respectively) but no changes in the hand-washing and sanitation practice. Conclusion The study findings show that: 1. the community-based health education has been evaluated to be effective in enhancing existing level of relevant knowledge and attitude as part of their preparedness toward communicable diseases related to flood 2. this research furthers contribute by providing customized and comprehensive community-based health education modules in preventing potential communicable disease outbreaks in affected flood-prone communities 3. this will reduce the costs associated with the diseases and reduce the vulnerabillties of communities exposed to floods